Seasonal contribution of dewfall to mercury deposition determined using a micrometeorological technique and dew chemistry. Issue 1 (9th January 2014) - Converse, Amber D.; Riscassi, Ami L.; Scanlon, Todd M.
<x xml:space="preserve">Abstract</x> [1] Deposition of mercury (Hg) to dew is thought to influence the diurnal dynamics of Hg species in the near‐surface air, yet this depositional pathway is not well characterized and is seldom accounted for in Hg budgets. This study quantifies Hg deposition to dew on a seasonal basis at a high‐elevation meadow in Shenandoah National Park, Virginia, and compares these rates with those for wet deposition and other forms of dry deposition. Dew samples were collected on a surrogate surface and analyzed for Hg concentrations (ng L−1), and dew depths (mm) were calculated using a micrometeorological approach based on the surface energy budget over 1 week period during each of the four seasons. Concentrations of Hg in dew (mean: 5.57 ng L−1) were lower than those observed in precipitation (mean weekly composite samples: 8.80 ng L−1). When dew deposition was scaled to the seasonal and annual levels, Hg deposition in dew was estimated to be 2–3 orders of magnitude smaller than wet deposition (estimated annual Hg deposition to dew/frost: 120 ng m−2; 2008 annual precipitation deposition: 12400 ng m−2). This disparity is attributed to the much lower dewfall amounts. Rates of Hg accumulation in dew were not related to gaseous elemental mercury (GEM) concentrations in the atmosphere nor were they related to measured GEM fluxes. They were, however, found to be similar to independently estimated rates of gaseous oxidized mercury (GOM) and particulate mercury (Hgp) deposition during the nighttime, suggesting that dew scavenges GOM and HgP from the atmosphere at the study site.